(untitled) (Biological Sciences - PJSIR, 2007)
The aq ueou s extract of leea guineensis leaves was eval uated for its an ti-edematogenic properties.The phytochemical studies revealed the presence of saponins and glycosides as the secondary metabo l i tes. Using the carrageenan induced paw oedema, there was a significant (P<0.001 ) reduction i n edema . The study a l so revea l ed a dose dependent anti edematogenic activity